2022
DOI: 10.1002/ajim.23399
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of suicide among farmers and ranchers: Using the CDC NVDRS 2003–2018

Abstract: Background Suicide is among the top 10 causes of premature death in the United States. This study provides details on farmer and rancher suicide decedents, including demographic information, mental health status, history of suicidal thoughts and attempts, and circumstances associated with death. Methods Data for this study were obtained from the Centers for Disease Control and Prevention's National Violent Death Reporting System Restricted Access Database for the years 2003–2018. Descriptive statistics and adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 38 publications
(100 reference statements)
0
6
0
Order By: Relevance
“…The number of workplace fatalities by suicide reached the highest level on record in 2019 (the most recent year for which data are available) 7 . Research at the national and international levels have indicated specific industries may be more vulnerable to suicide or suicide ideation, including first responders, 8 agriculture, 9 and construction 10 . In addition to the psychological impact on the employees, families, and communities of the person who died by suicide, workplace suicides incur a significant economic cost due to medical, legal, and lost earnings due to premature mortality 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…The number of workplace fatalities by suicide reached the highest level on record in 2019 (the most recent year for which data are available) 7 . Research at the national and international levels have indicated specific industries may be more vulnerable to suicide or suicide ideation, including first responders, 8 agriculture, 9 and construction 10 . In addition to the psychological impact on the employees, families, and communities of the person who died by suicide, workplace suicides incur a significant economic cost due to medical, legal, and lost earnings due to premature mortality 11,12 …”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, not surprising that this environmental hazard is very frequently involved with suicides within the farming population. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, not surprising that this environmental hazard is very frequently involved with suicides within the farming population. 15,16 Agricultural values and culture are additional important considerations when exploring risk factors for suicide among farmers. Farmers often have great pride in their occupation, show a strong bond to their often multi-generational farms, and feel a sense of responsibility to their families to continue their work.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that farmers in several countries experience a variety of health problems, often with epidemiological characteristics that differ from other occupations [8][9][10]. Working farmers have been found to be disproportionately affected by occupational injuries [11,12], chronic musculoskeletal problems [13,14], chronic respiratory conditions [15][16][17][18], depression, anxiety and suicide [19][20][21][22][23][24], and a general reduced quality of life in older age [25]. The gender and age demographics of farming populations, as well as socio-cultural characteristics, are amongst possible factors being explored [26,27].…”
Section: Introductionmentioning
confidence: 99%